PENGELOLAAN PRAKTEK KERJA INDUSTRI (PRAKERIN) SISWA JURUSAN PERHOTELAN SMK NEGERI 6 PADANG - Asnidar Asni; Yuliana Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
The background of this research, the low impact resulting from the activities of Industrial Work Practices (PRAKERIN) Students Programs Hospitality SMKN 6 Padang, This looks at the mistakes that occurred in the industry such as the student could not comply with the rules established in the hotel some hotels are return students back to school and there are also students who make a quiet Testament error made and supply activities preparation of students not prakerin according to what will be done in the industry, This type of research is qualitative descriptive method ata collection techniques are observation, interview and documentation. The data analysis technique that is data reduction, display data, conclusion and verification .The results of this study portray that (1) Planning a briefing given to the students is still less than the maximum. (2) The implementation of activities of Industrial Work Practices own good, but the implementation there are students who are lazy. (3) prakerin ratings given to tutor students are nice, but for the procedure of granting the student prakerin value assessment takes time to ask.Because to get that value students must complete the assigned activity journal from the beginning.